The Effect of Physical Therapy on Regional Lung Function in Critically Ill Patients - Eimer, Christine; Freier, Katharina; Weiler, Norbert; Frerichs, Inéz; Becher, Tobias (Frontiers in Physiology, 2021)
Early mobilization has become an important aspect of treatment in intensive care medicine, especially in patients with acute pulmonary dysfunction. As its effects on regional lung physiology have not been fully explored, we conceived a prospective observational study (Registration number: DRKS00023076) investigating regional lung function during a 15-minute session of early mobilization physiotherapy with a 30-minute follow-up period. The study was conducted on 20 spontaneously breathing adult patients with impaired pulmonary gas exchange receiving routine physical therapy during their intensive care unit stay. Electrical impedance tomography (EIT) was applied to continuously monitor ventilation distribution and changes in lung aeration during mobilization and physical therapy. Baseline data was recorded in the supine position, the subjects were then transferred into the seated and partly standing position for physical therapy. Afterwards, patients were transferred back into the initial position and followed up with EIT for 30 minutes. EIT data were analysed to assess changes in dorsal fraction of ventilation (%dorsal), end-expiratory lung impedance normalized to tidal variation (dEELI), centre of ventilation (CoV) and global inhomogeneity index (GI index). Follow-up was completed in 19 patients. During exercise, patients exhibited a significant change in ventilation distribution in favour of dorsal lung regions, which did not persist during follow-up. An identical effect was shown by CoV. dEELI increased significantly during follow-up. In conclusion, mobilization led to more dorsal ventilation distribution, but this effect subsided after returning to initial position. End-expiratory lung impedance increased during follow-up indicating a slow increase in end-expiratory lung volume following physical therapy.